Recent development of advanced processing technologies for biodiesel production: A critical review - Bashir, Muhammad Aamir; Wu, Sarah; Zhu, Jun; Krosuri, Anilkumar; Khan, Muhammad Usman; Ndeddy Aka, Robinson Junior (Fuel processing technology, 2022)
To move away from fossil fuels, biodiesel provides a sustainable alternative to addressing the socioeconomic and sustainable fuel problems. For biodiesel to be competitive, significant research has been focused on developing new and sustainable biodiesel production technologies to increase productivity. In this review, a comprehensive summary of the most recent developments in biodiesel production technologies was presented, including feedstocks, catalysts, reactors, and new processing technologies developed in recent years. The review showed that homogeneous and heterogeneous acid and base catalysts could achieve >90% conversion in biodiesel yield, while for enzymatic catalysts, it varied widely from around 70% to 99%, depending upon the feedstock type. Assisted by catalysts and alcohols, both batch and continuous flow reactors could achieve conversion yields by at least 89%. Also discussed were emerging technologies for biodiesel production, including plasma, microwave, and supercritical and ultrasonic radiation, along with the design process in membrane, microchannel, and reactive distillation reactors. Among the emerging technologies, the liquid-phase plasma discharge method was found to be most promising, reaching 99.5% yield in converting soybean oil to biodiesel in the shortest reaction time (seconds). In addition, the advantages and disadvantages of these emerging technologies were also reviewed. •A comprehensive review of recently developed biodiesel production technologies is presented.•Advanced reactors and processes are needed for different feedstocks.•Non-thermal plasma induced transesterification/esterification processed for biodiesel production is promising.•The mechanisms for some processes such as non-thermal plasma discharge needs to be further studied.